Method in the madness: teaching of English Literature in Japanese Universities - Zawiah Yahya (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
This paper explores the problematics of teaching English Literature in an EFL context. The analysis is based on class-observations and interviews with students and teachers in six Japanese universities over a period of nine months. The focus is on issues of English proficiency and literary competence, on choices made for medium, material and method, and on problem-solving measures taken to reduce the ‘foreignness’ of English literary texts. Among the measures looked at are the current use of the grammar-translation method and the inclusion of various support/introductory/survey courses built into the English Studies programme as an attempt to close the students’ proficiency-comprehension-knowledge gaps. Among the more contentious issues discussed are related to the wisdom of transplanting the canon of Western universities into non-English-speaking institutions, the appropriateness of imported teaching methodologies and the absence of local perspective input.